COMPANY EXTERNAL FUNDING TO GENERATE PROFIT - Vargo Christian L. Tobing; Erni Yanti Natalia (Universitas Putera Batam, 2022)
The study aims to look at the effect of external funding on a company's ability to make a profit. The object of the research is PT Ultra Jaya Milk Industry, Tbk. The data used is secondary data obtained from the idx.co.id website. The data studied is data from 2016 to 2020. From the results of the study, it can be known that the debt to equity ratio does not have a significant influence on the company's ability to obtain profits. The company's external funding (debt to equity ratio) in 2016 to 2019 has a stable value. But in 2020, the company's debt to equity ratio will increase significantly. As for the return on equity in 2016 to 2018 decreased. However, in 2019 to 2020, the company's return on equity increased.